Salt Lake Paper - Chloridizing Leaching at Park City (with Discussion) - Theodore P. Holt (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1915)
The Mines Operating Co.'s plant at Park City, Utah, was designed to treat the low-grade fillings in the old stopes of the Ontario mine. These fillings carry 6 to 14 oz. of silver, 1 to 2 lb. of copper, 0.01 to 0.015 oz. of gold, and a small percentage of lead and zinc. The treatment consists in mixing the crushed ore with coal dust and salt and then roasting in a new type of furnace by combustion of the contained fuel. The roasted ore is leached with an acid salt solution to dissolve the silver, gold, copper, and lead. At present these metals are precipitated together on scrap iron and the product sold to a refinery. The only new feature of importance in this scheme of treatment is the roasting process, which makes possible the chloridizing of ores without any loss of the valuable metals, and at a very low cost. History of the Development of the Process The roasting process- had its beginning in connection with research work at the Utah State School of Mines. N. C. Christensen, Jr., who held one of the School of Mines' fellowships, was engaged in some experimental work on blast roasting. At the same time I was doing some work on the insoluble gold in Mercur base ores. Mr. Christensen roasted some of this base gold ore in his pot furnace, and found that when he mixed a sufficiently low percentage of fuel with the ore, it did not sinter but roasted to a leachable product. We considered this a new application of blast roasting, and proceeded to test out a large number of ores in several different types of small roasters which we constructed.. This experimental work continued well into the summer of 1911. In August, 1911, the Consolidated Mercur Gold Mines Co. installed a small roaster of our design, which we proposed to operate on the counter-current principle, feeding mixed ore continuously on top, and at the same time drawing off the roasted ore from the bottom. By proper adjustment we hoped to maintain a permanent roasting zone near the center of the column, the ore moving downward as roasted. However, we